1999
DOI: 10.1002/(sici)1096-9896(199903)187:4<446::aid-path267>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

In situ expression patterns of melanoma-inhibiting activity (MIA) in melanomas and breast cancers

Abstract: Elevated levels of melanoma‐inhibiting activity (MIA) were measured previously in the serum of patients with metastasized melanomas and in a subgroup of patients with advanced‐stage breast cancers. This study aimed therefore to visualize in situ expression patterns of MIA protein and mRNA in melanomas and breast cancers by means of immunohistochemistry, reverse transcription‐polymerase chain reaction (RT‐PCR), and in situ hybridization. Analysis of a panel of seven common melanocytic naevi, ten cutaneous melan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 15 publications
1
44
0
Order By: Relevance
“…21 Immunohistochemical staining of ErbB-2 was performed using HercepTest (DAKO, Glostrup, Denmark) as described before. 22 Evaluation of immunohistochemical staining Evaluation of HercepTest was performed observing the staining pattern of cell membranes as set in the criteria specified by Dako for interpretation.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…21 Immunohistochemical staining of ErbB-2 was performed using HercepTest (DAKO, Glostrup, Denmark) as described before. 22 Evaluation of immunohistochemical staining Evaluation of HercepTest was performed observing the staining pattern of cell membranes as set in the criteria specified by Dako for interpretation.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Later, it was shown that MIA is expressed in malignant melanomas and chondrosarcomas (Bosserhoff et al, 1996(Bosserhoff et al, , 1999. Today, increased serum levels of MIA serve as a reliable clinical marker to detect and monitor metastatic disease in patients with malignant melanomas (Bosserhoff et al, 1997;Stahlecker et al, 2000), indicating an important role for them in tumor progression and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Virtually all primary and metastatic melanoma cells, but not normal melanocytes, express and secrete MIA to a high extent, such that MIA serum levels serve as a marker for malignant melanoma (Bosserhoff et al, 1997b, a;Deichmann et al, 1999). Neoplastic expression of MIA has also been observed in mammacarcinoma (Bosserhoff et al, 1999b), ovarian cancer (Bosserhoff et al, 1999a), and various gastrointestinal carcinomas (Wagner et al, 2000). Although MIA is thought to play an important role in cartilage formation, the cellular actions of MIA are not clear.…”
Section: Introductionmentioning
confidence: 99%